How can African agriculture adapt to climate change: The impact of climate change and adaptation on food production in low-income countries: Evidence from the Nile Basin, Ethiopia - Yesuf, Mahmud; di Falco, Salvatore; Deressa, Temesgen T.; Ringler, Claudia; Kohlin, Gunnar (International Food Policy Research Institute, 2008)
Growing consensus in the scientific community indicates that higher temperatures and changing precipitation levels resulting from climate change will depress crop yields in many countries over the coming decades. This is particularly true in low-income countries, where adaptive capacity is low. Many African countries are particularly vulnerable to climate change because their economies largely depend on climate-sensitive agricultural production. This brief is based on a study that used household survey data to analyze the impact of climate change on food production in the Nile Basin of Ethiopia. The study also examined the factors influencing adaptation and the implications of various adaptation strategies for farm productivity.